METAPHOR AND ITS FUNCTION IN LINGUISTICS: A COGNITIVE, SEMANTIC, AND PRAGMATIC EXPLORATION WITH REFERENCE TO THE LEXEME HONESTY (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Metaphor occupies a central position in contemporary linguistic theory, not merely as a rhetorical ornament but as a fundamental mechanism of conceptualization and meaning construction. Modern research in cognitive linguistics has demonstrated that metaphor structures human thought, organizes abstract domains, and shapes discourse practices. This article provides an expanded theoretical discussion of metaphor from semantic, cognitive, pragmatic, and cultural perspectives. Special attention is devoted to the metaphorical structuring of the lexeme honesty, illustrating how moral abstraction becomes cognitively accessible through embodied and culturally embedded source domains such as light, cleanliness, straightness, and solidity. The study argues that metaphor performs constitutive functions in linguistic representation and moral cognition.